2011
DOI: 10.1080/10826068.2011.547347
|View full text |Cite
|
Sign up to set email alerts
|

ZINGIPAIN, A CYSTEINE PROTEASE FROMZingiber ottensiiVALETON RHIZOMES WITH ANTIPROLIFERATIVE ACTIVITIES AGAINST FUNGI AND HUMAN MALIGNANT CELL LINES

Abstract: The objective of this study was to investigate the activity of a protein identified as cysteine protease, purified from Zingiber ottensii Valeton rhizomes, in terms of antiproliferation against fungi, bacteria, and human malignant cell lines. By means of buffer extraction followed by (NH(4))(2)SO(4) precipitation and ion-exchange chromatography, the obtained dominant protein (designated F50) was submitted to non-denaturing and reducing sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Microbes and animals are currently the major source of proteases with only a few commercialised plant proteases. Interest has been growing in plant proteases, which have significant commercial values due to high stability in extreme conditions ( Canay, Erguven & Yulug, 1991 ; Houde, Kademi & Leblanc, 2004 ; Karnchanatat et al, 2011 ). Examples of proteases from plant sources are listed in Table 4 .…”
Section: Secreted Proteases In Different Families Of Carnivorous Planmentioning
confidence: 99%
“…Microbes and animals are currently the major source of proteases with only a few commercialised plant proteases. Interest has been growing in plant proteases, which have significant commercial values due to high stability in extreme conditions ( Canay, Erguven & Yulug, 1991 ; Houde, Kademi & Leblanc, 2004 ; Karnchanatat et al, 2011 ). Examples of proteases from plant sources are listed in Table 4 .…”
Section: Secreted Proteases In Different Families Of Carnivorous Planmentioning
confidence: 99%
“…Furthermore, it was shown that the pupae of Aedes aegypti and Culex quinquefasciatus mosquitoes were susceptible to ZO essential oil [28]. For an aspect of anti-cancer properties, it has reported that Zingipain, which is a cysteine protease isolated and purified from Zingiber ottensii rhizomes, possessed relatively strong antiproliferative effects against cancer cell lines including hepatocellular carcinoma, HEP-G2 (IC50 = 1.13 µg/mL), and colon cancer, SW620 (IC50 = 5.37 µg/mL) [15]. However, there had previously been no investigation for the anti-cancer activities of the essential oil from Zingiber ottensii at the signaling pathway level to explain its molecular mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…The species is traditionally used as a sedative remedy for convulsion and as a lumbago treatment in Malaysia. In Thailand, Z. ottensii has been traditionally used to treat external bruises and gastrointestinal ulcers (Karnchanatat et al, 2011). Rungsaeng et al (2013) investigated the inhibitory potential of AChE of the rhizome aqueous extract (obtained from ammonium sulfate), and proteases isolated from Z. ottensii.…”
Section: Zingiber Ottensii Valetonmentioning
confidence: 99%